SIZE DISTRIBUTION OF PELAGIC FISHES IN THE JAVA SEA BY MEANS OF TARGET STRENGTH ANALYSIS - Bambang Sadhotomo (Indonesian Fisheries Research Journal, 2007)
This study aims to provide information on spatial distribution of fish size of pelagic community in the Java Sea. lt was based on target strength data observed during the acoustic cruises made by Research Vessel Bawal Putih in the years 1992 until 1994 and October 2005, using dual beam and split beam echosounder operated at 120 Khz.